2016
DOI: 10.4269/ajtmh.16-0236
|View full text |Cite
|
Sign up to set email alerts
|

Overlap in the Seasonal Infection Patterns of Avian Malaria Parasites and West Nile Virus in Vectors and Hosts

Abstract: Abstract. Multiple vector-borne pathogens often circulate in the same vector and host communities, and seasonal infection dynamics influence the potential for pathogen interactions. Here, we explore the seasonal infection patterns of avian malaria (Haemosporida) parasites (Plasmodium and Haemoproteus) and West Nile virus (WNV) in birds and mosquitoes in suburban Chicago. We show that both pathogens vary seasonally in Culex mosquitoes and avian hosts, but that patterns of covariation are complex. Different puta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 71 publications
(113 reference statements)
1
10
0
Order By: Relevance
“…Despite the absence of data about mosquitoes in CLBI to allow us to correctly evaluate the vector-parasite-host relationship, the positive association observed between temperature and Plasmodium prevalence may be related to the effects of temperature on the vectors of this parasite. For avian haemosporidians, the temperature is commonly described as an important abiotic factor influencing the parasite development and vector breeding opportunities ( Beier, 1998 ; Santiago-Alarcon, Palinauskas & Schaefer, 2012 ; Medeiros et al, 2016 ; Mordecai et al, 2019 ). It has been demonstrated that the development of different malaria parasites in vectors can be influenced by the climate and is generally hampered by low increments in temperature ( LaPointe, Goff & Atkinson, 2010 ; Zamora-Vilchis, Williams & Johnson, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the absence of data about mosquitoes in CLBI to allow us to correctly evaluate the vector-parasite-host relationship, the positive association observed between temperature and Plasmodium prevalence may be related to the effects of temperature on the vectors of this parasite. For avian haemosporidians, the temperature is commonly described as an important abiotic factor influencing the parasite development and vector breeding opportunities ( Beier, 1998 ; Santiago-Alarcon, Palinauskas & Schaefer, 2012 ; Medeiros et al, 2016 ; Mordecai et al, 2019 ). It has been demonstrated that the development of different malaria parasites in vectors can be influenced by the climate and is generally hampered by low increments in temperature ( LaPointe, Goff & Atkinson, 2010 ; Zamora-Vilchis, Williams & Johnson, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…There was also no association between prevalence and rainfall or, except for migratory behavior, any tested species-specific traits (diet, foraging strata, period of activity, species body weight, and nest shape). It is true that many studies have shown that different host-traits and abiotic factors are important determinants in a host-parasite interaction ( Ricklefs et al, 2005 ; Wood et al, 2007 ; Medeiros et al, 2016 ; Ferreira Junior et al, 2017 ; Hernández-Lara, González-García & Santiago-Alarcon, 2017a ; Ishtiaq, Bowden & Jhala, 2017 ; Fecchio et al, 2017b ; Eastwood et al, 2019 ). However, there are many variations in these studies’ results, and some of them fail to detect these interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The establishment that the infection in a vector is influenced by multiple factors, including alimentary behavior, seasonal effects and pathogen cooccurrence is recent (Ricklefs et al, 2016 ). Transcriptomic analyses provide the information to better address the intermediate steps between genes and their biological roles (Wang et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, one of the explanations for coinfection is that both pathogens can be transmitted at the same time by the same mosquitos. Medeiros et al [ 76 ] identified the presence of WNV and avian Plasmodium in mosquito pools in Chicago and found that WNV infection was positively related to Plasmodium infection. However, given that in this case, the data for mosquitoes were pooled, it is unclear whether or not the same or different individuals harbored both pathogens.…”
Section: Introductionmentioning
confidence: 99%